Study of Compatibility between Trichoderma harzianum and Carbendazim Fungicide using Poisoned Food Technique (International Journal of Food and Nutritional Sciences, 2022)
Trichoderma harzianum is a well-known biocontrol agent widely utilized for its antagonistic properties against various plant pathogens. Carbendazim is a synthetic fungicide commonly used in agricultural practices to control fungal diseases. To ensure sustainable and effective disease management strategies, it is crucial to assess the compatibility of these two agents when used together. The present study aims to evaluate the compatibility of Trichoderma harzianum with different concentrations Carbendazim fungicide viz., 200 ppm, 400 ppm, 600 ppm, 800 ppm and 1000 ppm using the poisoned food technique. The findings of the present study will contribute to understanding of potential synergistic or antagonistic effects of combining biocontrol agents and synthetic fungicides for enhanced disease control in agriculture.